Melatonin modifies basal and stimulated insulin secretion via NADPH oxidase. Issue 3 (December 2016) - Simões, Daniel; Riva, Patrícia; Peliciari-Garcia, Rodrigo Antonio; Cruzat, Vinicius Fernandes; Graciano, Maria Fernanda; Munhoz, Ana Claudia; Taneda, Marco; Cipolla-Neto, José; Carpinelli, Angelo Rafael
Abstract : Melatonin is a hormone synthesized in the pineal gland, which modulates several functions within the organism, including the synchronization of glucose metabolism and glucose-stimulated insulin secretion (GSIS). Melatonin can mediate different signaling pathways in pancreatic islets through two membrane receptors and via antioxidant or pro-oxidant enzymes modulation. NADPH oxidase (NOX) is a pro-oxidant enzyme responsible for the production of the reactive oxygen specie (ROS) superoxide, generated from molecular oxygen. In pancreatic islets, NOX-derived ROS can modulate glucose metabolism and regulate insulin secretion. Considering the roles of both melatonin and NOX in islets, the aim of this study was to evaluate the association of NOX and ROS production on glucose metabolism, basal and GSIS in pinealectomized rats (PINX) and in melatonin-treated isolated pancreatic islets. Our results showed that ROS content derived from NOX activity was increased in PINX at baseline (2.8 mM glucose), which was followed by a reduction in glucose metabolism and basal insulin secretion in this group. Under 16.7 mM glucose, an increase in both glucose metabolism and GSIS was observed in PINX islets, without changes in ROS content. In isolated pancreatic islets from control animals incubated with 2.8 mM glucose, melatonin treatment reduced ROS content, whereas in 16.7 mM glucose, melatonin reduced ROS and GSIS. In conclusion, our results demonstrate that both basal and stimulated insulin secretion can be regulated by melatonin through the maintenance of ROS homeostasis in pancreatic islets.